Construction of Novel CdS/SnNb2O6 Heterojunctions with Enhanced Photocatalytic Degradation Activity Under Visible Light. Issue 44 (26th November 2018) - Wu, Wen; Xuan, Yawen; Jin, Yu; Liang, Ximeng; Meng, Suci; Chen, Min
Abstract : ‐Accelerating the photo‐induced charge carrier transfer and improving charge utilization are critical for enhancing the photocatalytic activity of photocatalysts. In this work, we successfully constructed CdS/SnNb2 O6 heterojunction photocatalysts by a facile hydrothermal method. The obtained CdS/SnNb2 O6 heterojunction exhibited better photocatalytic performance than pristine CdS and SnNb2 O6, and the photocatalytic activity of the optimal ratio sample (40 % CdS) was 3.2 and 28.5 times as high as that of the pristine CdS and SnNb2 O6, respectively. On the basis of the PL spectra, transient photocurrent response, trapping experiments of the active species, and ESR results, the possible charge carrier transfer and photocatalytic mechanisms of the CdS/SnNb2 O6 heterojunction photocatalyst have been illustrated. We demonstrated that the combination of CdS and SnNb2 O6 can greatly boost the photo‐generated charge carrier separation and therefore enhance the photocatalytic activity. Our work opens up a new insight for development of semiconductor photocatalysts with high efficiency. Abstract : CdS/SnNb2 O6 heterojunction photocatalysts with enhanced photocatalytic performance have been developed, where the CdS can greatly boost the photo‐generated charge separation.